2019
DOI: 10.3390/pharmaceutics11050246
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Nanocapsules as a Platform for Needle-Free Vaccination

Abstract: Vaccination faces many challenges nowadays, and among them the use of adjuvant molecules and needle-free administration are some of the most demanding. The combination of transcutaneous vaccination and nanomedicine through a rationally designed new-formulation could be the solution to this problem. This study focuses on this rational design. For this purpose, new hyaluronic acid nanocapsules (HA-NCs) have been developed. This new formulation has an oily nucleus with immunoadjuvant properties (due to α tocopher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The HA-based nanomaterials were also employed to deliver antigens in a needle-free administration route. Bussio et al [ 250 ] found that OVA-loaded HA nanovaccines could be absorbed through skin thus no needles were involved in this process to avoid risks of injuries and infections. However, more studies are needed to confirm the in vivo therapeutic efficacy of the HA-based nanovaccines through this needle-free approach.…”
Section: Hyaluronic Acid-based Nanomedicinesmentioning
confidence: 99%
“…The HA-based nanomaterials were also employed to deliver antigens in a needle-free administration route. Bussio et al [ 250 ] found that OVA-loaded HA nanovaccines could be absorbed through skin thus no needles were involved in this process to avoid risks of injuries and infections. However, more studies are needed to confirm the in vivo therapeutic efficacy of the HA-based nanovaccines through this needle-free approach.…”
Section: Hyaluronic Acid-based Nanomedicinesmentioning
confidence: 99%
“…Nanoparticles, due to their size, can penetrate the epidermal tissue, and their high specific surface can express a high quantity of antigen, sufficient for the generation of an immune response. Nanocapsules of approximately 100nm in size were synthetised by Bussio et al using chitosan [20] or hyaluronic acid [4], Both systems show a good skin penetration and a good retention of the model proteins without affecting the cell viability in ex vivo studies.…”
Section: Topical Administrationmentioning
confidence: 99%
“…• Due to the many functional groups displayed, polysaccharides can be easily functionalised with many functional molecules such as antigens [4] or can form polyelectrolytic complexes with different polymers [5].…”
Section: Introductionmentioning
confidence: 99%
“…This polymer is produced via extraction from rooster combs and through bacterial fermentation. It is recognized by a variety of receptors, including the receptor for hyaluronic acid-mediated motility (RHAMM) [ 129 ], transmembrane protein layilin, hyaluronic acid receptor for endocytosis (HARE), lymphatic vessel endocytic receptors (LYVE-1) [ 130 ], and intracellular HA-binding proteins, including CDC37, RHAMM/IHABP, P-32, and IHABP4 [ 131 ]. Moreover, it interacts with dermal DCs and epidermal Langerhans cells through HA receptors, TLR2, and TLR4 present in immune cells [ 132 ].…”
Section: Carbohydrate-based Adjuvantsmentioning
confidence: 99%
“…HA has been explored as a potential adjuvant for antigen delivery due to its immune-stimulating properties and its ability to form nanoparticles via electrostatic interaction with cationic components (cationic polymers, or some lipidic formulations). HA-coated nanoparticles are able to promote DC activation and maturation, enhance co-stimulatory molecules such as CD40 and CD86, induce antigen-specific CD4 + and CD8 + T-cell responses, stimulate the secretion of cytokines, facilitate robust antigen-specific IgG antibody production, and enhance memory T-cell generation [ 129 , 134 ]. Nanoparticles were formed by ionic interaction between TMC and HA (321 nm, +13 mV).…”
Section: Carbohydrate-based Adjuvantsmentioning
confidence: 99%